(untitled) (Journal of Pharmaceutical Negative Results, 2022)
60 extracted single rooted premolar human teeth were used in this study. The canal spaces of all the teeth were prepared with a round bur (1.3mm diameter). The specimens were sectioned horizontally at the mid root level dentin into 1.5±0.2 mm thick slices. The slices were randomly divided into 2 groups (n=30), group 1- Biodentine and group 2- MTA. The samples were wrapped in wet gauze, placed in an incubator, and were allowed to set for 10 min at 37°C with 100% humidity. After incubation, the samples in each group were divided into 5 subgroups to be immersed into irrigants (NAOCL, MTAD, QMIX, SMEAR CLEAR AND SALINE). After 30 min of immersion, all samples of Group 1 and Group 2 were removed from the test solutions, rinsed with distilled water, and allowed to set for 48 h at 37°C with 100% humidity in an incubator. The push out bond strength values were measured by using a universal testing machine. One-way Analysis of Variance (ANOVA), Post hoc Tukey test and independent test were used for statistical analysis in the present study. Biodentine showed greater pushout bond strength than MTA. Among the irrigants saline showed the highest pushout bond strength followed by NAOCL>MTAD>smear clear>Qmix.